Repetitive Transcranial Magnetic Stimulation Delivered With an H‐Coil to the Right Insula Reduces Functional Connectivity Between Insula and Medial Prefrontal Cortex. Issue 3 (23rd October 2019) - Lee, Mary R.; Caparelli, Elisabeth C.; Leff, Michelle; Steele, Vaughn R.; Maxwell, Andrea M.; McCullough, Karen; Salmeron, Betty Jo
Abstract : Objective: Insula neurocircuitry alterations are reported in a range of neuropsychiatric disorders holding promise for clinical interventions. We measured, in a pilot study, acute neuroplastic modulations resulting from high‐ and low‐frequency stimulation with repetitive transcranial magnetic stimulation (rTMS) delivered via an H‐coil that targeted the right insula and overlying prefrontal cortex. Methods: Healthy, nonsmoking, adult participants ( N = 28), in a within‐participant, sham‐controlled experiment, received a single rTMS session on four separate days. Participants received one session each of low‐ (1 Hz) and high (10 Hz)‐frequency stimulation and two sessions of sham stimulation matched to each rTMS frequency. After each rTMS session, participants completed a functional magnetic resonance imaging (fMRI) scan while performing two cognitive tasks and a resting‐state scan. The effect of rTMS was examined on task behavior as well as blood oxygenated level‐dependent (BOLD) response during task performance and resting state. We expected low‐ and high‐frequency stimulation to decrease and increase, respectively, insula and overlying cortical BOLD signal and network connectivity. Results/Conclusions: There was no effect of rTMS, regardless of frequency, on task behavior or task‐based BOLD response. There was an effect of rTMS compared to sham on rsFC between insula and medial prefrontal cortex, with connectivity reduced after rTMS compared to sham, regardless of frequency. Implications for using rTMS to the insula as a treatment for neuropsychiatric disorders are discussed in light of insula‐medial prefrontal cortex connectivity.